Hybrid foldamer with unique architecture from conformationally constrained aliphatic-aromatic amino acid conjugate - Srinivas, Deekonda; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Tetrahedron, 2006)
In this paper, we describe the design and synthesis of a novel hybrid foldamer, derived from a conformationally constrained aliphatic-aromatic amino acid conjugate that adopts a well-defined, compact, three-dimensional structure, governed by a combined conformational restriction imposed by the individual amino acids from which the foldamer is composed. Conformational investigations confirmed the prevalence of a unique doubly bent conformation for the foldamer, in both solid and solution states, as evidenced from single crystal X-ray and 2D NOESY studies, respectively. The findings suggest that constrained aliphatic-aromatic amino acid conjugates offer new avenues for the de novo design of hybrid foldamers with distinctive structural architectures. Furthermore, the de novo design strategy disclosed herein has the potential for significantly augmenting the `tool-box' of the modern day peptidominetic chemist, as well as providing a novel approach to the field of rational design. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Conformation; Foldamer; Peptidomimetics

Helical self-assembly of molecules in pseudopolymorphs of racemic 2,6-di-O-(4-halobenzoyl)-myo-inositol 1,3,5-orthoformates: clues for the construction of molecular assemblies for intermolecular acyl transfer reaction - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2010)
The crystal structure of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate (1) which underwent a facile intermolecular benzoyl transfer reaction in the solid state, revealed a helical assembly of molecules along the two-fold screw axis via O-H center dot center dot center dot O hydrogen bond bringing the electrophile (C=O) and the nucleophile (-OH) in close proximity along the helical axis. However, structurally related racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (2) and chloro (3)) produced triclinic dimorphs (both P (1) over bar) when crystallized from methanol and ethyl acetate. Molecules in either form did not assemble spirally (like 1), and instead exhibited a one-dimensional isostructurality, bridging O-H center dot center dot center dot O linked identical molecular strings via C-H center dot center dot center dot O interactions across the inversion center. However, the molecules of 2 and 3 assembled in a helical manner similar to 1 with inclusion of solvent molecules in the crystal lattice when crystallized from other common organic solvents. Remarkably, in all the solvates the host molecules formed strikingly similar helices around the crystallographic 2(1)-screw axis through O-H center dot center dot center dot O bond involving the -OH group and carbonyl oxygen of the equatorial C2-O-benzoyl group. Comparison of the crystal structure of dimorphs and the solvatomorphs revealed that the solvent molecules, which interact with the orthoformate-bridge, trigger the helix formation of the host. The difference in the crystal structures of solvatomorphs arises in the interlinking of the neighbouring helices, which creates voids of different sizes to accommodate the solvent molecules. All the solvates crystallized in the monoclinic system distributed over three different space groups P2(1)/n, P2(1)/c and C2/c. In the P2(1)/n system, the adjacent helices are linked via C-X center dot center dot center dot O contacts, in P2(1)/c via C-H center dot center dot center dot X (X Cl, Br) contacts and in C2/c via short X center dot center dot center dot X contacts (X = Cl). The helical organization achieved through solvent mediation and inclusion is of significance in creating molecular packing for intermolecular acyl transfer reactions in crystals.

Halogen bonding in 2,5-dichloro-1,4-benzoquinone: insights from experimental and theoretical charge density analysis - Hathwar, Venkatesha R.; Gonnade, Rajesh G.; Munshi, Parthapratim; Bhadbhade, Mohan M.; Row, Tayur N. Guru (Crystal Growth & Design, 2011)
Experimental charge density distribution in 2, 5-dichloro-1, 4-benzoquinone has been carried out using high resolution X-ray diffraction data at 90 K to quantitatively evaluate the nature of C-Cl center dot center dot center dot O=C halogen bond in molecular crystals. Additionally, the halogen bond is studied from geometrical point of view and the same has been visualized using Hirshfeld surface analysis. The obtained results from experimental charge density analysis are compared with periodic quantum calculations using B3LYP 6-31G(d,p) level of theory. The topological values at bond critical point, three-dimensional static deformation density features and electrostatic potential isosurfaces unequivocally establish the attractive nature of C-Cl center dot center dot center dot O=C halogen bond in crystalline lattice.

Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.

Highly enantioselective Pd-catalyzed synthesis of P-stereogenic supramolecular phosphines, self-assembly, and implication - Koshti, Vijay S.; Mote, Nilesh R.; Gonnade, Rajesh G.; Chikkali, Samir H. (Organometallics, 2015)
Metal-catalyzed asymmetric addition of a secondary phosphine to an aryl halide is one of the most efficient and reliable approaches for the construction of enantiopure carbon phosphorus bonds. An isolated Pd(II) complex (5) catalyzes the carbon phosphorus coupling reaction between tolylphenylphosphine (la) and 3-iodophenylurea (2b), which proceeds with an unprecedented enantiomeric excess (ee) of 97%. The generality of the strategy has been demonstrated by preparing a small library of a new class of P-stereogenic phosphines with an in-built hydrogen bonding motif for the first time. The P-stereogenic phosphines self-assemble on a metal template via deliberately installed hydrogen-bonding motifs and mimic the bidentate ligand coordination. Interestingly, when it was employed in asymmetric hydrogenation, the supramolecular phosphine {1-(3-(phenyl(o-toly)phosphanyl)pheny)ureal} (6b) produced the corresponding hydrogenated product with the highest enantiomeric excess of 99% along with excellent conversion, demonstrating the potential of these enantioenriched P-chirogenic supramolecular phosphines in asymmetric catalysis.

H-Bonding assisted self-assembly of anionic and neutral ligand on metal: a comprehensive strategy to mimic ditopic ligands in olefin polymerization - Mote, Nilesh R.; Patel, Ketan; Shinde, Dinesh R.; Gaikwad, Shahaji R.; Koshti, Vijay S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2017)
Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-association of anionic ligand 3-ureidobenzoic acid (2a) and neutral ligand 1-(3-(diphenylphosphanyl)phenyl)urea (1a) on a metal template to yield metal complex [{COOC6H4-NH(CO)NH2}{Ph2PC6H4NH(CO)NH2}PdMeDMSO] (4a). The identity of 4a was established by NMR and mass spectroscopy. Along the same lines, 3-(3-phenylureido)benzoic acid (2b) and 1-(3-(diphenylphosphanyl)phenyl)-3-phenylurea (1b) self-assemble on a metal template to produce palladium complex [{COOC6H4NH(CO)NHPh}{Ph2PC6H4NH(CO)NHPh}PdMePy] (5c). The existence of 5c was confirmed by Job plot, 1-2D NMR spectroscopy, deuterium labeling, IR spectroscopy, UV-vis spectroscopy, model complex synthesis, and DFT calculations. These solution and gas phase investigations authenticated the presence of intramolecular hydrogen bonding between hydrogen's of 1b and carbonyl oxygen of 2b. The generality of the supramolecular approach has been validated by preparing six complexes from four monodentate ligands, and their synthetic utility was demonstrated in ethylene polymerization. Complex 4a was found to be the most active, leading to the production of highly branched polyethylene with a molecular weight of 55700 g/mol and melting temperature of 112 degrees C.

Harnessing nucleophilicity of allenol ester with p-quinone methides via gold catalysis: application to the synthesis of diarylmethine-substituted enones - Sharma, Brijesh M.; Rathod, Jayant; Gonnade, Rajesh G.; Kumar, Pradeep (Journal of Organic Chemistry, 2018)
A gold(I)-catalyzed protocol for intermolecular 1,6-conjugate addition of nucleophilic allenol ester generated in situ through [3,3]-sigmatropic rearrangement with p-quinone methides (p-QMs) has been developed. The gold catalyst plays a dual role by the pi-acid-triggered activation of alkynes and at the same time as a Lewis acid for activation of p-QMs toward nucleophilic attack. This method enables rapid access to a wide range of densely functionalized diarylmethine-substituted enones, a Morita-Baylis-Hillman (MBH) product with high selectivity, excellent yields, and broad substrate scope.

Helically structured peptide architecture engineered using dimedone as a rigid organic scaffold - Nadimpally, Krishna C.; Madica, Krishnaprasad; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
This communication reports the use of a rigid organic scaffold to attach two unsymmetrical peptide chains on a single carbon atom. The approach describes the step-by-step attachment of peptide chains to the rigid dimedone template (5,5-dimethyl-1,3-cyclohexanedione) - a molecular scaffold that directs orientation of the peptide helices in a well-defined arrangement via intra-molecular hydrogen bonding. The overall topology of the final molecules was studied using CD spectroscopy which suggested existence of helical architecture.